Airway dysfunction and Inflammation in Pool- and Non-Pool-Based Elite Athletes - Martin, N.; Lindley, M. R.; Hargadon, B.; Monteiro, W. R.; Pavord, I. D. (Medicine & Science in Sports & Exercise, 2012)
Purpose: This study sought to determine and compare the levels of airway dysfunction and inflammation in a large cohort of symptomatic international athletes from pool- and non-pool-based sporting backgrounds. In total, 118 athletes were recruited.